JEJAK PERINTAH DALAM DOA DAN WAHYU: STUDI FI'IL AMR DALAM AYAT-AYAT PERMOHONAN DAN TITAH DALAM AL-QUR'AN - Akmaluddin; Elshandy Surya Pratama (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study explores the semantic functions of fiʿil amr in the Qur’an, focusing on two key contexts: supplicatory (prayer) and declarative (divine command) verses. While grammatically imperative, fiʿil amr in Qur’anic usage serves multiple functions such as request, advice, and warning. Using a qualitative content analysis method, the research identifies, classifies, and analyzes relevant verses semantically and pragmatically with reference to classical and modern exegetical sources. The findings reveal that the meaning of fiʿil amr is context-dependent, shaped by communicative roles between God, the Prophet, and believers. This study contributes to the field of Qur’anic linguistics and promotes a contextual approach in interpretation.